Physico-chemical properties of Kenyan made calcined Clay -Limestone cement (LC3). (June 2020) - Marangu, Joseph Mwiti
Abstract: In Kenya fired clay bricks are mainly used as construction materials. However, vast quantities of these Fired Rejected Clay Bricks (FRCB) generated are rejected annually as a result of improper calcination or demolition of housing units made of clay bricks. These FRCB are largely disposed off in open fields leading to land pollution. This paper reports the experimental findings on the performance of Limestone Calcined Clay Cement (LC3). The test cement was prepared by blending and inter-grinding of clinker, FRCB, limestone and gypsum. Saturated lime test was used to assess the pozzolanic activity of LC3. Mortar prisms measuring 40 mm x 40 mm x 160 mm were cast using LC3 at a water/cement (w/c) ratio of 0.50, 0.55 and 0.60. The casted mortars were cured in water for a period of 2, 7 and 28 day separately. Compressive strength tests were conducted at each of the testing ages on the cured mortar prisms. The cured mortars were also subjected to porosity and chloride ingress tests. Compressive strength measurements were also taken after exposure of 28-day cured mortar prisms in 3.5% sodium chloride solution in accelerated chloride ingress in a laboratory set-up. For comparison purposes, all the aforementioned tests were also conducted using commercial Ordinary Portland Cement (OPC) and Portland Pozzolana Cement (PPC). The results showed that LC3 and PPC were pozzolanic while OPC was non-pozzolanic. Furthermore, there was significant difference in terms of compressive strengths between LC3 and OPC at all the curing ages. In addition, LC3 exhibited lower porosity, chloride ingress in terms of chloride diffusion coefficients compared to PPC and OPC. Increased w/c ratio resulted in increased porosity, chloride ingress while compressive strength decreased. In conclusion, FRCB was found to be potential raw material for the production of LC3 in Kenya.